How Entrepreneurial Mindset, Gender Stereotypes, and Innovation Practices Influence the Sustainability of Women-Owned Businesses in Bogor City, Indonesia - Hakim, Nur; Ode, Haruni; Rahmadhani, May Vitha; Naim, Sidrotun (International Journal of Business, Law, and Education, 2024)
This study investigates the influence of entrepreneurial mindset, gender stereotypes, and innovation practices on the sustainability of women-owned businesses in Bogor City, Indonesia. Using a sample of 200 women entrepreneurs, data was collected through structured questionnaires and analyzed using multiple regression analysis. The results indicate that entrepreneurial mindset and innovation practices positively impact business sustainability, while gender stereotypes have a negative effect. The findings emphasize the critical role of fostering a strong entrepreneurial mindset and encouraging innovation among women entrepreneurs, while also addressing the detrimental impact of gender stereotypes on business operations. The study contributes to the growing body of literature on women’s entrepreneurship and offers practical insights for policymakers and support organizations in creating a conducive environment for the sustainability of women-owned businesses